Water-Column, Sediment, and in Situ Chronic Bioassays with Cladocerans - Pereira, Anabela M. M. (2000)
In situ bioassays are becoming very popular for laboratory test validation and field extrapolation. Natural conditions, including environmental variables, affect the "behavior" of contaminants and, consequently, their toxicity. This work aimed to develop protocols for in situ chronic bioassays with cladocerans and to assess the ecological relevance of conventional protocols for laboratory testing (water-column and sediment). An aquatic system impacted with acid mine drainage was chosen for the study. At some stations that were contaminated with heavy metals, water-column bioassays did not reveal any toxicity, while sediment and, especially in situ bioassays, revealed a delay in reproduction and a reduction in fertility. Thus, both laboratory bioassays underestimated the actual toxicity of studied sites: sediment, besides being an important contaminant source, became significantly altered with sampling, transport, storage, and manipulation. Therefore, an extra caution is needed when interpreting laboratory results, since the extrapolation to natural systems could be a very problematic step.